ANALYSIS OF PAVEMENT DRAINAGE SYSTEM: A CASE STUDY ALONG BURE TO INJIBARA TOWN ROAD SECTION IN AMAHRA REGION - Bayou, Hailu Terefe; Lemu, Dumesa Gudissa; Fenta, Asnakew Melku (Journal of Civil Engineering, Science and Technology, 2025)
Moisture has significantly influenced the performance of flexible pavements. Effective drainage systems are essential for maintaining pavement integrity by rapidly removing moisture from the subgrade. This study investigates the drainage system of the Bure to Injibara road in Ethiopia's Amhara region, focusing on identifying the root causes of drainage issues and evaluating the quality of the pavement layers. Data were collected from both primary and secondary sources, including site visits and field studies. Descriptive and experimental research methodologies were employed to assess the current drainage conditions and understand the underlying issues. The descriptive analysis centered on the existing pavement drainage system and factors contributing to drainage inefficiencies. Laboratory tests were conducted on selected sections to evaluate the properties of pavement material layers. The Drainage Requirements in Pavement (DRIP) Software was used to assess drainage quality, and the direct runoff for specific rainfall events was estimated using the soil conservation service (SCS) curve number method. The key finding indicates that the cross-slope time-to-drain is rated as good, while the uniform slope time-to-drain is fair. Visual inspections, material sampling, and laboratory investigations identified critical issues, including climatic conditions, inadequate pavement material properties, the absence of inlets, improper disposal of solid waste into the drain, poor construction quality, environmental impacts, topographical challenges, and suboptimal drainage characteristics. Specific drainage problems included low drain capacity, soil accumulation, lack of inlets, improper waste disposal, and malfunctioning crossing culverts. The study recommends adherence to design manuals, regular maintenance schedules, cleaning, and systematic cleaning to enhance drainage performance. Additionally, the redesign and reconstruction of drainage facilities are proposed to mitigate issues related to poor workmanship. The results show that flexible pavements without drainage layers lead to fully saturated subgrades, compromising their performance. Incorporating drainage layers and edge drains significantly reduces subgrade moisture content, thereby enhancing pavement durability and performance.